A Model of Maslahah Performance for Higher Education Institution: Case of Institut Agama Islam Tazkia - Herdiansyah, Hera; Firdaus, Achmad; Tarmizi, Erwandi (AL- IKTISAB Journal of Islamic Economic Law, 2019)
There are several programs under the Ministry of Research, Technology and Higher Education and Ministry of Religious Affairs of the Republic of Indonesia in many areas which decreased its performance level until it ended at the closing of the operational permit and even the revocation of the college permits concerned. Organizational performance is a series of performance starting from level of the organization, working units to individuals. The research on performance organization uses university based on maslahah with case study at Institut Agama Islam Tazkia. Purpose this study aims to develop a performance model based on maslahah using the framework of BAN-PT Accreditation, Maslahah Performance (MaP), and Quality Management System (QMS) ISO 9001. Methods of collection of sample are purposive sampling. Primary data collection techniques by collecting documentation directly and by distributing questionnaires to the ranks of the lecturers and the management of STEI Tazkia. Data analysis techniques by calculating the results of the questionnaire with Likert scale. The results showed that the development model of performance began with the preparation of the vision and mission, strategic objectives. It is suggested to all universities that offer the program of Islamic economics, finance, banking, and accounting; it should have a good vision, mission and objective.